Anticoagulation instability with life-threatening complication after dietary modification. Issue 780 (October 1990) - Chow, W. H.; Chow, T. C.; Tse, T. M.; Tai, Y. T.; Lee, W. T.
Abstract : Anticoagulation instability due to a change in intake of vitamin K after dietary modification was observed in 2 patients on long-term oral anticoagulants. One patient developed diffuse bruises treated conservatively with fresh frozen plasma transfusion and the other had a thrombosed aortic prosthesis which required emergency operation. To prevent such complications, dietary modification especially with food rich in vitamin K should be undertaken with care in patients on long-term oral anticoagulants.